O ideal corporal da magra saudável: norma médica e resistências do feminino na anorexia - Martins, Mayara Magalhães (2010)
This dissertation is a sociological study about young girls stricken with nervous anorexia attending a medical service that specializes in the treatment of alimentary disorders. Based on cases related by three youths, this work aims at presenting conflicting aspects that those patients had to go through during their medical treatment. It is investigated how anorexic subjects display a body that is considered healthy by medical science. To this end it was engaged as main support the work of Michel Foucault. Based on his concept of resistance, it is sought to unveil how anorexic patients produce their subjectivities in dealing with medical knowledge and information obtained from the media about health, well being and beauty. In the same fashion, this works is interested in discovering how production of genre identity appears in the process of renouncing a prepubescent body in order to adopt a sexually mature body. Based on a qualitative approach, especially from data obtained from field research, it was possible to observe that the anorexic experience is essentially a paradoxical feature. The production of an anorexic body into a healthy body requires rearrangements going from the will of keeping an excessively slender figure and the desire of obtaining cure. Based on statements from anorexic subjects it is possible to assert that the disorder is both a manisfestation of disagreement presented by these girls in their attempt at building a feeling of autonomy by reining their feeding drives and the plentiful offer of discourses about health, beauty and diets in order to elect just one of these discourses as their guidance to a way of life